From Authority to Autopsy: How Translations Reflect Changing Scientific Norms - Elsherif, Garda (chronotopos – A Journal of Translation History, 2024)
This paper examines translations of books in the natural sciences into French from the sixteenth to the eighteenth centuries. Specifically, it examines the scientific reader’s expectations of contemporary book translations. To that end, this study investigates review reports on manuscripts of translations submitted to the leading French institution of modern sciences—the Académie Royale des Sciences. These are compared to review reports of manuscripts of translations submitted to the Faculté de Médecine of the Paris University, which remained longer in the pre-modern attempt to preserve classical ‘auctores’ in translation. The comparison of the review reports reveals interesting shifts in translation norms, highlighting the demand for critical scientific translations wherein the translator, as a member of the scientific community, critically investigates and comments on the translated text.